Reservas de carbono orgánico en suelos con cultivo de nogal en Belén, Catamarca - Nieto, Maria Isabel; De Bustos, Maria Eugenia; Bulacios Muñiz, Olivia del Valle; Brizuela, Luisa Elena; Bellanich, Augusto Exequiel (Asociación Argentina Ciencia del Suelo, 2024)
Póster